Bio-psycho-social concept of ageing - Prodović, Tanja T.; Ignjatovic-Ristić, Dragana; Prodović, Biljana T. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The paper focuses thematically on one of the essential issues of human existence, a complex and a mysterious phenomenon of ageing. The old people with their biological and psychological features, with their social position and other aspects, are the inexhaustible source of professional research of doctors and sociologists. As opposed to the usual pessimistic attitude of ageing and the old age, the paper points, within the humanist and social work frame, to man’s awareness of overcoming the transience of human existence by cultivating a sense and a beauty of life. By elaborating on the concept of ageing, the authors stress the length and the quality of life, which could be advanced by the interaction of three groups of factors: social engagement and participation, the reduction of illness and the improvement of the high level of psychological and mental functions.
Keywords: health issues; SOCIAL ISSUES; demography; AGEING; old age